2021
DOI: 10.31014/aior.1993.04.02.259
|View full text |Cite
|
Sign up to set email alerts
|

Music Teachers’ Burnout Levels in terms of Some Variables

Abstract: The Education Quarterly Reviews is an Open Access publication. It may be read, copied, and distributed free of charge according to the conditions of the Creative Commons Attribution 4.0 International license.The Asian Institute of Research Education Quarterly Reviews is a peer-reviewed International Journal. The journal covers scholarly articles in the fields of education, linguistics, literature, educational theory, research, and methodologies, curriculum, elementary and secondary education, higher education,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
(38 reference statements)
1
2
0
Order By: Relevance
“…The study also found that teachers' emotional intelligence levels are not affected by their years of service in the profession. Studies that reach similar results are identified in the literature (Arteaga-Cedeño et al, 2022;Gürol, 2008;Ertuğrul, 2020;Öztürk, 2006), but there are also studies that reach different conclusions.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The study also found that teachers' emotional intelligence levels are not affected by their years of service in the profession. Studies that reach similar results are identified in the literature (Arteaga-Cedeño et al, 2022;Gürol, 2008;Ertuğrul, 2020;Öztürk, 2006), but there are also studies that reach different conclusions.…”
Section: Discussionsupporting
confidence: 55%
“…Using the age variable as a variable for the research, it was determined that emotional intelligence levels of preschool teachers are not different. Upon reviewing the literature, similar studies were found (Dumitriu et al, 2014;Ertuğrul, 2020;Gürol, 2008;Öztürk, 2006;Öztürk & Deniz, 2008). In the study by Arteaga-Cedeo et al (2022) on preschool and primary school teachers, it was found that emotional perception levels, one of the factors of emotional intelligence, decrease with age.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation